2012
DOI: 10.1007/s12687-012-0104-2
|View full text |Cite
|
Sign up to set email alerts
|

Preconception exposure to mutagens: medical and other exposures to radiation and chemicals

Abstract: Contrary to intuition, no environmental exposure has been proved to cause human germ line mutations that manifest as heritable disease in the offspring, not among the children born to survivors of the American atomic bombs in Japan nor in survivors of cancer in childhood, adolescence, or young adulthood who receive intensive chemotherapy, radiotherapy, or both. Even the smallest of recent case series had sufficient statistical power to exclude, with the usual assumptions, an increase as small as 20 % over base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…Further analysis revealed that older people are at a 3.1 times higher risk when carrying SNP309, which could potentially explain the increased incidence of lung cancer in the elderly (Table 4). It was also observed that men were at 2.24 times higher risk in comparison to female when carrying SNP309, which may reflect the accumulative effects of exposure to higher levels of mutagens [36][37][38]. Many studies have reported that smokers carrying SNP309 are at a significantly increased risk of lung cancer, and our results are in agreement with the studies showing 2.77 times higher risk with smoking, as well [39].…”
Section: Discussionsupporting
confidence: 91%
“…Further analysis revealed that older people are at a 3.1 times higher risk when carrying SNP309, which could potentially explain the increased incidence of lung cancer in the elderly (Table 4). It was also observed that men were at 2.24 times higher risk in comparison to female when carrying SNP309, which may reflect the accumulative effects of exposure to higher levels of mutagens [36][37][38]. Many studies have reported that smokers carrying SNP309 are at a significantly increased risk of lung cancer, and our results are in agreement with the studies showing 2.77 times higher risk with smoking, as well [39].…”
Section: Discussionsupporting
confidence: 91%
“…This is not the case for animal studies, in which mating is continuous regardless of treatment. This difference may help explain the negative results in the human cancer studies 5556…”
Section: Discussionmentioning
confidence: 99%
“…This information is important for counseling cancer survivors planning to have children. Mulvihill55 discusses preconception exposure to mutagens covering medical and other exposures to radiation and chemicals. Winther et al 56.…”
Section: Paternal Exposure To Chemicalsmentioning
confidence: 99%
“…Epidemiological evidence including exposure to genotoxins (radiation and chemotherapy) in girls prior to puberty shows that potential damage to primordial follicles by DNA damaging agents does not cause an increase in birth defects in their subsequent offspring. 26 Upon onset of puberty, a 5-to 6-month oocyte maturation cycle is initiated. At any given time, several oocytes are undergoing maturation.…”
Section: Based On Genetic Toxicity Datamentioning
confidence: 99%